2021
DOI: 10.3390/ma14185290
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sn Addition on Zn-Al-Mg Alloy; Part II: Corrosion Behaviour

Abstract: Corrosion behaviour of Sn (0.0, 0.5, 1.0, 2.0 and 3.0 wt.%)-doped Zn 1.6 wt.% Al 1.6 wt.% Mg alloys exposed to salt spray testing was investigated. Intergranular corrosion was observed for all alloys in both as-cast and annealed states. However, due to microstructure spheroidisation in the annealed samples, potential intergranular corrosion paths are significantly reduced. Samples with 0.5 wt.% of Sn showed the best corrosion properties. The main corrosion products identified by XRD analysis for all samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Recently, zinc-aluminum-magnesium (Zn-Al-Mg) coatings have been innovated through hot-dip plating technology, which has attracted more and more attention due to its excellent corrosion resistance and self-healing capabilities [4,5,[12][13][14]. Previous studies have indicated that the addition of Mg and Al elements to the molten bath undergoes eutectic reactions, resulting in the generation of various alloy phases such as MgZn 2 , which may form the Zn/MgZn 2 binary eutectic phase or Zn/Al/MgZn 2 ternary eutectic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, zinc-aluminum-magnesium (Zn-Al-Mg) coatings have been innovated through hot-dip plating technology, which has attracted more and more attention due to its excellent corrosion resistance and self-healing capabilities [4,5,[12][13][14]. Previous studies have indicated that the addition of Mg and Al elements to the molten bath undergoes eutectic reactions, resulting in the generation of various alloy phases such as MgZn 2 , which may form the Zn/MgZn 2 binary eutectic phase or Zn/Al/MgZn 2 ternary eutectic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc-aluminum-magnesium coatings are generally divided into three categories (a low-aluminum series with an Al content of 1.0-2.5 wt.%, a medium-aluminum series with an Al content of 6.0%-11 wt.%, and a high-aluminum series with an Al content of 50%-60 wt.%) [6][7][8]. The main research object of this study was low-aluminum coatings, which are currently also the most widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…After MgZn 2 dissolves, it provides Mg 2+ cations and reacts with OH − to form Mg(OH) 2 precipitates, while Zn 2+ and Zn(OH) 2 eventually form ZnO. The precipitation of Mg(OH) 2 lowers the pH value, thereby creating the thermodynamic conditions for the formation of the water-insoluble simonkolleite (Zn 5 Cl 2 (OH) 8 •H 2 O) [13][14][15]. However, partial studies show that due to the relatively poor stress-strain behavior of MgZn 2 , it is easy to produce cracks during deformation processing, which leads to a decrease in the material performance.…”
Section: Introductionmentioning
confidence: 99%
“…The phase was found to be nobler than Mg 2 Zn 11 and MgZn 2 . Furthermore, we observed a local de-alloying of Mg 2 Sn particles [ 21 ]. The Mg concentration in Mg 2 Sn was gradually reduced during corrosion, resulting in the production of Sn-rich particles in place of Mg 2 Sn particles.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of compositional solid solubility constitutes an opportunity for designing Mg–Sn alloys with tunable electrochemical properties. Most previous studies have investigated the effect of Sn concentration in selected solid solution Mg 100x –Sn x alloys (x = 1–3 at.%) on their electrochemical performance in chloride-containing electrolytes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Nevertheless, alloys with Sn concentration higher than 3 at.% have been significantly less explored.…”
Section: Introductionmentioning
confidence: 99%